EAS spectrum in the primary energy region above 10 to the 15th power eV by the Akeno and Yakutsk array data - Krasilnikov, D. D.; Knurenko, S. P.; Krasilnikov, A. D.; Sleptsov, I. Y.; Yegorova, V. P.; Pavlov, V. N. (1985)
The extensive air showers spectrum on scintillation desity Rko in primary energy region E sub approx. 10 to the 15th power - 10 to the 20th power eV on the Yakutsk array data and recent results of the Akeno is given.